Diagnosis and management of AL amyloidosis due to B-cell non-Hodgkin lymphoma - Berkowitz, Callie; Dittus, Christopher (Frontiers in Oncology, 2022)
Immunoglobulin light chain (AL) amyloidosis may be caused by a B-cell non-Hodgkin lymphoma (NHL) rather than a plasma cell neoplasm in rare cases, which presents unique diagnostic and management considerations. NHL associated with AL will often have an IgM paraprotein; thus, this disease is termed IgM-related AL amyloidosis (IgM AL). The clinical presentation of IgM AL is more likely to involve the lungs, peripheral nerves, and soft tissue; cardiac involvement is less common. Patients with IgM AL amyloidosis should undergo a lymphoma-directed work-up including evaluation for nodal and extranodal disease. Additionally, patients with an IgM paraproteinemia should be screened for AL amyloidosis through history and physical examination. Treatment regimens active against underlying lymphoma, rather than plasma cell-directed regimens, are recommended. Historical response rates in IgM AL have been poor; prospective studies of novel antineoplastic regimens may improve treatment outcomes.